2003
DOI: 10.1002/bse.344
|View full text |Cite
|
Sign up to set email alerts
|

The legislation of environmental disclosures in three Nordic countries—a comparison

Abstract: This paper compares the legislation in Denmark, Norway and Sweden concerning what kind of environmental information firms must disclose. These three Nordic countries have great similarities regarding accounting legislation and standards. However, Denmark has chosen a different way to force firms to disclose their environmental performance compared with Norway and Sweden. Danish firms must deliver separate ‘green accounts’, while Norwegian and Swedish firms are bound to report on environmental issues in the adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 18 publications
1
42
0
2
Order By: Relevance
“…This way, in 1993, CICA issued the regulation "Environmental Cost and Liabilities", establishing the accounting recognition and the disclosure of the future expenditures on removal and restoration of sites (environmental provisions) (Li and McConomy, 1999). Norway was the first European country to introduce environmental information on the annual report, through the Enterprise Act of 1989, which required the environmental disclosure in the annual reports of all companies involved in significant pollution businesses (Kolk, 1999;Nyquist, 2003b;Hibbit and Collison, 2004). Spain is also one of the pioneer countries in the EU, in terms of environmental accounting regulations (Criado Jiménez et al, 2008), with the approval of the 1998 Royal Decree 437/1998, of March 20th, concerning the adaptation of the General Accounting Plan to companies of the electrical sector, which made it mandatory for all Spanish companies to present the environmental information in the annual report.…”
Section: National Initiativesmentioning
confidence: 99%
See 1 more Smart Citation
“…This way, in 1993, CICA issued the regulation "Environmental Cost and Liabilities", establishing the accounting recognition and the disclosure of the future expenditures on removal and restoration of sites (environmental provisions) (Li and McConomy, 1999). Norway was the first European country to introduce environmental information on the annual report, through the Enterprise Act of 1989, which required the environmental disclosure in the annual reports of all companies involved in significant pollution businesses (Kolk, 1999;Nyquist, 2003b;Hibbit and Collison, 2004). Spain is also one of the pioneer countries in the EU, in terms of environmental accounting regulations (Criado Jiménez et al, 2008), with the approval of the 1998 Royal Decree 437/1998, of March 20th, concerning the adaptation of the General Accounting Plan to companies of the electrical sector, which made it mandatory for all Spanish companies to present the environmental information in the annual report.…”
Section: National Initiativesmentioning
confidence: 99%
“…As a consequence, since 1999, all companies that require environmental licences have to disclose information about the environmental impacts of their activities in the management report (Kolk, 1999;Nyquist, 2003a-b;Sinclair and Walton, 2003;KPMG and UNEP, 2006). In Denmark, since 1996, the Danish Environmental Protection Act requires companies to publish environmental information in the format of Environmental Report ("Green accounts") that should be submitted to local and governmental entities (Bebbington, 1999, Nyquist, 2003b. This legislation was revised in 2001 and 2002 to follow new international developments in environmental accounting and disclosure.…”
Section: National Initiativesmentioning
confidence: 99%
“…Many countries use, or consider using, some kind of reporting regulations (Nyquist 2003). Does regulation bring enterprises' environmental disclosure more in line with the characteristics of useful information (IASB 2010;Snavely 1967), or at least ensure a minimum of information?…”
Section: Introduction ˈIt Is Important To Note That In the Interactiomentioning
confidence: 99%
“…Longitudinal studies have shown that the introduction of, or changes in, regulations affect reporting (Criado-Jiménez et al 2007;Fallan and Fallan 2009;Frost 2007;Llena, Moneva, and Hernandez 2007). However, while studies usually consider only one type of regulation, e.g., an accounting standard or a legal requirement (Criado-Jiménez et al 2007;Frost 2007;Larrinaga et al 2002;Llena, Moneva, and Hernandez 2007;Mobus 2005;Vormedal and Ruud 2009), regulation regimes often consist of a heterogeneous set of regulations from various sources (Melting and Tungen 2012;Nyquist 2003).…”
Section: Introduction ˈIt Is Important To Note That In the Interactiomentioning
confidence: 99%
“…Such smaller green manufacturing enterprises can be found all over the world; they care about their natural environment, who they are as manufacturers, and find green initiatives profitable. The second category consists of smaller manufacturing enterprises that initially made a low commitment to green initiatives and found it not interesting to renew [96][97][92][93][94][96][97][98][99][101][102][104][105][106][107][108]7,[12][13]28,47,57 Commitment,12,[19][20]22,[30][31][32][33][36][37][38][39][41][42][43][44][45][47][48][49][50][51][52][53][54][55][57][58][59][60][61][71]…”
mentioning
confidence: 99%